Quantum Optics Research Prospects: Transformation Towards Faster Quantum Computing - Uwe Barroso; Mahon Nitin; Snyder Bradford (Yayasan Adra Karima Hubbi, 2024)
Advancements in quantum computing have become a primary focus in modern computer science. However, one of the major challenges in creating more powerful quantum computers is developing more stable and efficient qubits. In this context, research in quantum optics offers game-changing solutions. By leveraging quantum physics principles and quantum optics technology, this research aims to transform the quantum computing landscape by creating more stable and faster qubits. The goal of this study is to explore the potential of quantum optics in creating more stable and efficient qubits for quantum computing. This research method involves a combination of experimental and theoretical approaches. Data obtained from these experiments will be analyzed using advanced theoretical methods to understand the quantum properties of the produced qubits. The results indicate that the quantum optics approach can be key in creating more stable and faster qubits for quantum computing. Experiments have successfully demonstrated better control over qubits in photonic systems and compressed matter, producing qubits with higher reliability. Theoretical analysis also reveals a deeper understanding of the quantum properties of the produced qubits, opening the door for further development in this field. The conclusion of this research shows that quantum optics has great potential to transform quantum computing by creating more stable and faster qubits. By continuing to develop quantum optics technology and deepening the understanding of quantum properties of compressed matter and photonic systems, quantum computing can be taken to a new level.